2019
DOI: 10.1177/0333102419869319
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind placebo-controlled randomized clinical trial of ginger (Zingiber officinale Rosc.) in the prophylactic treatment of migraine

Abstract: Background Previous studies have shown an analgesic effect of ginger in the acute treatment of migraine, and there is anecdotal evidence of its efficacy in migraine prophylaxis. Objective This study aimed to evaluate the potential of ginger to prevent migraine attacks. Methods This double-blind, placebo-controlled randomized clinical trial took place at the Headache Clinic, Universidade Federal de Minas Gerais (Belo Horizonte, Minas Gerais, Brazil), involving 107 patients. Only subjects diagnosed with episodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Also, a traditional herbal formulation containing P. emblica had similar protective effects on MH during a 3-month intervention [ 66 ]. Also, a clinical trial showed that a 3-month use of the Z. officinalis extract significantly decreased the frequency of migraine attacks [ 42 , 67 ]. However, the effect of ginger on headache severity was not significantly different from that of placebo or sumatriptan [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a traditional herbal formulation containing P. emblica had similar protective effects on MH during a 3-month intervention [ 66 ]. Also, a clinical trial showed that a 3-month use of the Z. officinalis extract significantly decreased the frequency of migraine attacks [ 42 , 67 ]. However, the effect of ginger on headache severity was not significantly different from that of placebo or sumatriptan [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zingiberone, curcumene, bisrabolone, α-pinene, β-pinene, limonene, p-cymene, α-terpineol, and verticiole [82,83]. Prokinetic, antiulcer, carminative, anti-dyspeptic, Useful for nausea relief, decrease pressure on the lower oesophagal sphincter, reduce intestinal cramping, and stimulate antral contractions in healthy people individuals and gastrotonic [63,67,83].…”
Section: Zingiber Ofcinalismentioning
confidence: 99%
“…Experimental studies demonstrate that Ginger inhibits the synthesis of the pro-inflammatory mediators, prostaglandin and nitric oxide in porcine chondrocytes, and Leukotriene in vitro, which in clinical terms, could result in a reduction in the level of pain, and inflammation [3,51]. Ginger has a pain-relieving effect and can control pain via a variety of pathways, including prostaglandin suppression via the (cyclooxygenase) COX and (lipoxygenase) LOX pathways, antioxidant action, inhibition of the transcription factor (nuclear factor kappa-lightchain-enhancer of activated B cells) nf-kB, or acting as a vanilloid nociceptor agonist [36,49,50,52].…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated with a dose 400 mg of ginger showed significantly better clinical response, suggesting a beneficial effect on migraine attack (Martins et al, 2019). However, the same authors found that ginger had not benefit in the prophylactic treatment of migraine when compared to placebo in a double‐blind, placebo‐controlled RCT carried out in patients who received capsules three times per day of 200 mg of dry extract of ginger (Martins et al, 2020).…”
Section: Antiinflammatory and Analgesic Effectsmentioning
confidence: 99%